The Root Causes of Lumbar Canal Stenosis: An Insight with a Narrative Review - Ankit Jaiswal; Rameez Bukhari; Prateek Upadhyay (Journal of Clinical and Diagnostic Research, 2023)
In the older population, lumbar spinal stenosis is a frequent degenerative condition that can cause clinical symptoms such as neurogenic claudication or sciatica, either with or without low back pain. Anatomically, there are three different forms of lumbar spinal stenosis: central, foraminal, and lateral recess. The relationship between Ligamentum Flavum (LF) hypertrophy and mechanical stress, as seen in segmental instability or disc space expansion, and their correlation with lumbar facet joint arthropathy is still not clear. This review places particular emphasis on the causes like LF hypertrophy, lumbar segmental instability, lumbar segmental motion, disc degeneration, lumbar spine facet joint orientation, facet joint tropism and facet joint Osteoarthritis (OA) in Lumbar Canal Stenosis (LCS) studied in various different studies discovered in various other search databases. The present research will also help surgeons and radiologists to interpret neuroradiological data appropriately for surgery as well as non surgical treatment and get a better knowledge of the architecture of these structures and how they appear on neuroimaging investigations for further proper and apt management of LCS. Additionally, it would assist in creating a diagnostic algorithm for better functional results.